2021
DOI: 10.1002/mabi.202100173
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Selective Impedimetric Determination of Prostate Specific Membrane Antigen Based on Di‐Succinimide Functionalized Polythiophene Covered Cost‐Effective Indium Tin Oxide

Abstract: A new and ultrasensitive impedimetric biosensor fabricated by using conjugated di‐succinimide substituted polythiophene (P(ThidiSuc)) polymer modified indium tin oxide electrode is developed for the first time to detect the prostate specific membrane antigen (PSMA). The polymer P(Thi‐diSuc) is synthesized by using a simple way and used in the fabrication of the proposed biosensor. The synthesized polymer contains di‐succinimide groups, which offers covalent immobilization of PSMA specific antibodies. The devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…These electrochemical variations are detectable by following the R ct that mostly rise with the amount in the quantity of target analytes attached onto the working electrode surface. [26][27][28][29] This study demonstrated the fabrication of EIS-based immunosensor for quantification of CALR in human serum samples. For designing of the immunosensor, a nanocomposite layer composed of amino substituted polypyrrole polymer (PPyNH 2 ) and rGO was coated on disposable and low-cost ITO electrode.…”
Section: Introductionmentioning
confidence: 83%
“…These electrochemical variations are detectable by following the R ct that mostly rise with the amount in the quantity of target analytes attached onto the working electrode surface. [26][27][28][29] This study demonstrated the fabrication of EIS-based immunosensor for quantification of CALR in human serum samples. For designing of the immunosensor, a nanocomposite layer composed of amino substituted polypyrrole polymer (PPyNH 2 ) and rGO was coated on disposable and low-cost ITO electrode.…”
Section: Introductionmentioning
confidence: 83%
“…Aydın et al (Figure 21) reported a novel and ultrasensitive impedimetric biosensor fabricated using conjugated di-succinimide substituted polythiophene (P(ThidiSuc)) polymer modified indium tin oxide electrode to detect the PSMA. [93] Studies have shown that PSMA is expressed in all types of prostate tissue and that expression is increased in cancerous tissues. [93] The synthesized polymer (P(ThidiSuc)) contains di-succinimide groups, which offered covalent immobilization of PSMA specific antibodies and did not require any cross-linking agent.…”
Section: Other Biomarkers-based Biosensors (Including Dual-biomarkers...mentioning
confidence: 99%
“…[93] Studies have shown that PSMA is expressed in all types of prostate tissue and that expression is increased in cancerous tissues. [93] The synthesized polymer (P(ThidiSuc)) contains di-succinimide groups, which offered covalent immobilization of PSMA specific antibodies and did not require any cross-linking agent. Under optimum conditions, a wide linear range (0.015 to14.4 pg mL −1 ), and an LOD of 6.4 fg mL −1 were achieved.…”
Section: Other Biomarkers-based Biosensors (Including Dual-biomarkers...mentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility property of polypyrrole makes it a proper immobilization matrix material for binding of biorecognition molecules. Furthermore, polypyrrole can be synthesized with electrochemical polymerization on the electrode surface. , Polypyrrole, a particular conducting polymer with a high application potential, is a quite suitable candidate for the synthesis of nanotube composites and appropriate for being an immobilization matrix material . In a previous study, a polyaniline-SWCNT nanocomposite was synthesized on the working electrode, and the prepared electrode was utilized for detection of triglyceride .…”
Section: Introductionmentioning
confidence: 99%